Implementasi Kebijakan Sistem Zonasi Pada Tingkat Sekolah Dasar Negeri Dalam Pemerataan Pendidikan di Kota Surabaya - Ismail; Tri Prasetijowati; Crist Diva Sudona (Public Sphere Review, 2024)
The zoning system policy is a government program to achieve equitable education and to remove the public paradigm of superior schools and that all schools are superior. The purpose of this research is to analyze the implementation of the zoning system policy at the public primary school level and the factors that affect its implementation. In this research, the method used is a qualitative method with a descriptive approach. Based on the results of research on the zoning system policy at the public primary school level, the implementation of PPDB with zoning pathways in Surabaya public primary schools is in accordance with Permendikbud Number 1 of 2021. Viewed from the Edward III theory, this zoning system policy has been implemented well because of the public's understanding and the responsiveness of the parties involved in overcoming obstacles. However, there are still some people who still do not understand this zoning system policy due to uneven socialization.